ANALISIS POTENSI PAJAK PENGHASILAN ATAS BAGI HASIL YANG DIBAYARKAN MITRA GOFOOD KEPADA PERUSAHAAN GOJEK - Fajarizki Galuh (Badan Pendidikan dan Pelatihan Keuangan - Kementerian Keuangan Republik Indonesia, 2020)
The growth of many startup that provides various of product like application based technology makes economics activity more effective and efficient, such as Gojek. One of the best features that gojek has is gofood. Gofood facilitates its users to buy beverages via online. Because of that, many restaurant in Indonesia begin to become gofood’s partner. However, the existence of gofood’s partner still doesn’t contribute for tax income. This researches aim to analyze personal tax income of gofood’s partner potenty more deeply that focuses on KPP Pratama Jember’s administration area. This research uses qualitative approaches to collect data by interviewing some related interviewees.. According to research result, the growth of gojek application influences to increasing of gofood partner’s omzet.. So, this condition gives impact to increasing of personal income tax potenty. The personal income tax potenty consists of three aspect, such as income aspect, operation expense aspect, and sharing profit aspect. Directorate General of Taxation should designs a rules that manages taxation of gofood partner’s business process. This strategy is expected to increase tax revenue and contributes to development of this country in the future.